Electrophysiological Signatures of Perceiving Alternated Tone in Mandarin Chinese: Mismatch Negativity to Underlying Tone Conflict - Zeng, Yuyu; Fiorentino, Robert; Zhang, Jie (Frontiers in Psychology, 2021)
Although phonological alternation is prevalent in languages, the process of perceiving phonologically alternated sounds is poorly understood, especially at the neurolinguistic level. We examined the process of perceiving Mandarin 3rd tone sandhi (T3 + T3 → T2 + T3) with a mismatch negativity (MMN) experiment. Our design has two independent variables (whether the deviant undergoes tone sandhi; whether the standard and the deviant have matched underlying tone). These two independent variables modulated ERP responses in both the first and the second syllables. Notably, despite the apparent segmental conflict between the standard and the deviant in all conditions, MMN is only observed when neither the standard nor the deviant undergoes tone sandhi, suggesting that discovering the underlying representation of an alternated sound could interfere with the generation of MMN. A tentative model with three hypothesized underlying processing mechanisms is proposed to explain the observed latency and amplitude differences across conditions. The results are also discussed in light of the potential electrophysiological signatures involved in the process of perceiving alternated sounds.